Five new species of black coral (Anthozoa; Antipatharia) from the Great Barrier Reef and Coral Sea, Australia - Horowitz, Jeremy; Opresko, Dennis; Molodtsova, Tina N.; Molodtsova, Tina N.; Beaman, Robin J.; Cowman, Peter F.; Bridge, Tom C.l. (Zootaxa, 2022)
We describe five new species of black corals from the Great Barrier Reef and Coral Sea, collected at depths ranging from 14 to 789 m: two in the family Antipathidae (Antipathes falkorae sp. nov. and Antipathes morrisi sp. nov.), two in the family Aphanipathidae (Aphanipathes flailum sp. nov. and Rhipidipathes helae sp. nov.), and one in the family Cladopathidae (Hexapathes bikofskii sp. nov.). We also present a phylogeny of 80 black corals reconstructed from a target capture dataset of ultraconserved elements and exons, to show the systematic relationships among new and nominal species. This phylogeny also represents a backbone for future species descriptions and research into the evolutionary history of the Antipatharia.